The impact of peer feedback on English writing motivation and performance in middle school: a statistical analysis - Xuan, Y.; Nimehchisalem, V.; Md Yusof, Mohamad A. (Natural Sciences Publishing, 2024)
In recent years, teachers have gradually been returning the classroom to students, requiring students to change their learning styles and transform passive learning into active learning. Allowing students to self-assess and peer-to-peer feedback in the teaching process and building a good classroom environment can help promote active learning. Based on L2 Motivational Self System (L2MSS) and cooperative learning theory[15, 16], this paper makes a comparative experiment and questionnaire survey on a total of 90 students from two parallel classes in the second grade of a key middle school and then the data obtained were statistically analyzed using SPSS. Then to examine the role of peer feedback and classroom environment in increasing motivation to write in middle school English. The results show that peer feedback is an effective way for students to learn. Additionally, peer feedback can effectively encourage middle school students to improve their motivation to write in English and encourage them to learn writing more effectively. The paper concludes with a discussion of the implication of these results.